Subjective socioeconomic status and nutritional labels : do they influence our food choices and preferences? - Moh, Heng Gee (2019)
Past studies have proposed that one’s socioeconomic status as well as the presence of nutritional labels would affect the type of food items that people prefer. Hence, this study aims to investigate the effects and association between subjective socioeconomic status and nutritional labelling in people’s food choices. It is hypothesized that low SSES participants are more likely to prefer unhealthier food options that are paired without the Healthier Choice Symbol (HCS), while high SSES participants would prefer healthier food options paired with the HCS. Participants were manipulated into the low, control or high SSES conditions where they were required to make food choices in the Food Preference Task, and subsequently rate the food items presented in terms of liking, healthiness and fillingness. Results indicated that there was no main effect of SSES and participants in the low SSES conditions did not significantly differ from participants in the high SSES condition in terms of selecting healthier choice options. It was further demonstrated that participants also tend to prefer unhealthier food options without the Healthier Choice Symbol (HCS). Additionally, food items that were selected by participants in the Food Preference Task were also rated more preferably, being perceived as healthier and having greater fillingness. The findings of this study have widened our understanding of the motives behind food consumption behaviors, which are especially valuable in a world where obesity and health-related issues are rising.